The influence of human resource management (HRM) practices on service-oriented organizational citizenship behaviours (OCB): an explanatory sequential study - Thanigaivel R, Krishnan * (2019)
Nowadays, the utilisation of human resource management (HRM) practices is widely believed to influence employee organisational citizenship behaviour (OCB). However, there is lack of understanding on the mechanisms that relate HRM practices and service-oriented OCB, which is referred to as the “black box” in the context of telecommunications and Internet service-oriented organizations in Malaysia. Drawing on social exchange theory and ERG theory, this study discovered the mediating effect of employee job satisfaction on the relation between HRM practices and service-oriented OCB. Moreover, by integrating indirect relation with the theory of work adjustment, this study suggested that the proposed indirect relation between HRM practices and service-oriented OCB was stronger when person-organisation (PO) fit was implemented into the organisation. Therefore, this study also discovered the moderated mediation effect whereby PO fit moderated the strength of the mediated relation between HRM practices and service-oriented OCB via employee job satisfaction. This study adopted the explanatory sequential method to provide a deeper understanding of the research questions. The study started with the collection and analysis of quantitative data, and followed by collection and analysis of qualitative data. For quantitative study, a total of 204 self-administered questionnaires were collected from customer-contact employees who is working in telecommunication and Internet service providers in Malaysia. The mediation and moderated mediated hypotheses were analysed by PROCESS SPSS technique by using SPSS (Statistical Package for the Social Sciences) software. For the qualitative study, semi-structured interviews were conducted with 20 customer-contact employees who had initially participated in the quantitative study. In this study, thematic analysis was used to analyse the semi-structured interview data. The quantitative results showed that employee job satisfaction mediated the relation between HRM practices and service-oriented OCB organisations. Further, quantitative results of study also showed that the perceived PO fit moderated the strength of indirect relation between HRM practices (pay practice, employee security, and supervisor support) and service-oriented OCB via employee job satisfaction. Qualitative results of this study helped to validate the statistical analysis findings by identifying in what way employee satisfaction and employee expectation of HRM practices were affected by different factors. Finally, this study makes theoretical, methodological and practical contributions to the research on the influence of HRM practices on service-oriented OCB.